PARP goes the weasel! Emerging role of PARP inhibitors in acute leukemias. (January 2021) - Fritz, Claire; Portwood, Scott M.; Przespolewski, Amanda; Wang, Eunice S.
Abstract: Poly (ADP-ribose) polymerase (PARP) inhibitors, which induce synthetic lethality of BRCA mutant breast and ovarian cancers, are now under active exploration for treatment of acute leukemias, specifically acute myeloid leukemia (AML). Experimental data has revealed that DNA repair deficiencies similar to those found in BRCA mutant solid tumors function in malignant hematopoietic cells to enhance cell survival and promote therapy resistance. Preclinical studies have demonstrated that inhibition of PARP with a variety of agents can dramatically enhance the efficacy of other therapeutic approaches including cytotoxic and epigenetic chemotherapy, small molecule inhibitors (IDH and FLT3 inhibitors) and antibody drug conjugates. This has led to early stage clinical trials of multiple PARP inhibitors (PARPi) for AML patients. Despite small patient numbers, evidence of modest clinical efficacy and tolerability in combinatorial regimens support the further development of PARP inhibition as a novel therapeutic strategy for AML, particularly in select molecular subsets (MLL rearranged, FLT3 and IDH1 mutant disease.